Itinerant Ambassador : The Life of Sir Thomas Roe - Brown, Michael J., 1932- (Book collections on Project MUSE., 1970)
Thomas Roe, born near London in 1580 or 1581 was a notable and influential figure in the England of Elizabeth and of the early Stuarts. In his wide-ranging career, he came into contact with an array of famous seventeenth-century persons ranging from Sir Walter Raleigh to Archbishop William Laud and from Queen Elizabeth of Bohemia to the Great Mogul Emperor of Hindustan. Roe was one of the most capable diplomats of his time and his career was associated with developments of great importance: colonial and commercial expansion, the beginnings of empire, foreign relations, religious movements, dom.